Microwave ablation-assisted liver gene transfection in rats. (17th August 2016) - Jiang, Ruoyu; Meng, Lingkai; Sun, Longhao; He, Xianghui; Liang, Xiaoyu; Zhang, Jie; Zhang, Zhixiang
Abstract: Purpose: Thermal ablation has been used to manage liver malignancy. This study aimed to assess histological changes in rat liver after microwave ablation (MWA) and to investigate whether thermal damage caused by MWA on surrounding liver tissue enhances the efficiency of liver gene transfer. Methods: MWA was applied to rat liver, and the pathological tissue and ultrastructural changes were evaluated. Green fluorescent protein (GFP) and Renilla luciferase-expressing plasmids were administered to liver tissues by direct injection. GFP expression in liver tissue was analysed in frozen sections using an inverted fluorescence microscope, and Renilla luciferase expression in target tissue was determined using a luminometer. Results: Tissue demarcations were observed in liver tissue after ablation, and a transition zone with morphological changes was present between necrotic and normal tissue. Hepatocytes in the transition zone showed decreased numbers of microvilli on cell surfaces and increased extracellular space. GFP expression was observed in the transition zone after MWA and plasmid injection and lasted up to 7 days post-ablation. Both the fluorescence and luminescence levels in the transition zone of the liver tissue were significantly higher than those in the untreated tissue ( P < 0.001). Conclusions: Direct plasmid injection to the liver tissue of the transition zone after MWA can achieve effective gene transfection. These findings provide an experimental basis for exploring MWA-assisted target gene transfer for cancer gene therapy.